Improved filter design in internal model control: application to hybrid feed drive mechatronic system. (17th April 2022) - Touati, Nahla; Saidi, Imen; Soudani, Dhaou
In this paper, the internal model control (IMC) is proposed for overactuated systems for high frequency bands. To deal with redundancy, the method of virtual outputs is considered to square the system and design the controller obtained by a specific inversion technique. An improved low-pass filter is then inserted in the IMC structure in order to attenuate the sensitivity of the controller, improve the system performance and the robustness of the structure towards disturbances and uncertainties. The proposed filter design aims to increase the bandwidth of the system. Furthermore, to evaluate its efficiency, an application to control a mechanical linear system, namely hybrid feed drive system, is described. The obtained simulation results are shown to be satisfactory by considering a series of different scenarios.